Novos índices no domínio da frequência para avaliar a co-contração com base no eletromiograma - Andrade, Vanessa Santos de (2018)
Stroke causes motor changes, including increased co-contraction, which has been inferred from temporal indexes based on electromyography (EMG) signals. Estimating co-contraction rates in the frequency domain could provide relevant information. This work proposes new indexes to evaluate co-contraction based on the analysis of EMG signals in the frequency domain. EMG signals of extensor (2) and flexor (3) fingers muscles from healthy (n = 32) and post-stroke (13) individuals were recorded. The following were obtained: (a) ICM (f) - index during the execution of the movement; (b) ICR (f) - index between movements; and (c) ICD (f) - the relationship between these two indexes. The correlation between these indexes and the Fugl-Meyer (FM) was evaluated for the post-stroke group. There were identified three frequency ranges for the indexes (p < 0.05, with Bonferroni correction): Range 1 (from 40 to 160 Hz), Range 2 (from 160 to 300 Hz) and Range 3 (from 300 to 440 Hz). The indexes were significantly different between the groups, mainly the ICD (f), and their correlation was significant (≈ 0.9; p < 0.05) with the FM scores in post-stroke individuals. The new indexes proposed in this study were able to verify differences in the co-contraction between healthy and poststroke, besides they are promising to evaluate motor function in post-stroke individuals.